Head-out aquatic exercise “sailor’s jigs” kinematics at increasing musical cadence. - Teixeira, Genoveva (2016)
The aim of this study was to analyze the relationships between “Sailor’s jigs” kinematic and increasing music cadence. Six young women with at least one year of experience conducting this type of head-out aquatic programs, with no kind of skeletal muscle injury reported on the last six months and non-pregnant were evaluated. The exercise was recorded on video, in the frontal plane, using a pair of cameras, enabling a double projection, from above and underwater body motions, at five increasing cadences (120 b.min-1, 135 b.min-1, 150 b.min-1, 165 b.min-1 and 180 b.min-1). Images were thereafter digitized in specific software (Ariel Performance Analysis Systems). The cycle period decreased through the incremental protocol. Cycle period decrease is done decreasing joints range of motion and increasing the limbs segmental velocity as well. Although these combined kinematical strategy, a deeper analysis reveals that subjects decrease the cycle period mainly decreasing the range of motions.